The Online Branding Teh Botol Sosro - Krishnata - Sektiyono (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2018)
Sinar Sosro introduced their product, namely Fruit Tea, which was aimed at the youth segment, which at that time had not been touched by tea-type products. With the existence of Fruit Tea, Sosro tries to give a different new touch, namely by developing a tea with a fruit flavor. At that time abroad, tea drinks with fruit flavors were also becoming a trend there. Until now, fruit tea has various types of fruit flavors from apple, strawberry, lemon, mango to blackcurrant flavors. The fruit tea segment is for teenagers, and it is marketed mainly in Java, Sumatra, Kalimantan and Sulawesi. Their branding before implementing online branding used advertisements that were posted or aired on television stations, magazines, newspapers, radio, and various large and small events. In addition, Sosro distributes several billboards and the like to introduce their products to potential consumers and consumers. Teh Botol Sosro quickly adapts to the times so that they can reach a wider audience, especially the millennial generation by creating an Instagram account with the account name (@tehbotososroid) which already has more than 60 thousand followers and has posted more than 400 posts. PT. Sinar Sosro in applying digital branding to his company can be said to be successful in big cities, this is proven by the average number of sales of PT. Sinar Sosro in big cities is 32%, but less effective outside big cities. Then seen from their achievements in the previous few years and had become the market leader.